Communion Ecclesiology in a Racially Polarised South Africa - Resane, Kelebogile T. (UJ Press, 2017)
Communion Ecclesiology by Dr. K.T. Resane explores the concept of a communion ecclesiology in South Africa. The book provides the reader with a comprehensive overview of the concept in the Bible, in history and in different church traditions including the African Initiated Churches. The book also focuses on the different cultural groups in South Africa as they were organised within theological traditions. - Prof. S.D. Snyman, University of the Free State